Patient-Centered Obstetric Care in the Age of Cell-Free Fetal DNA Prenatal Screening. (March 2018) - Agatisa, Patricia K; Mercer, Mary Beth; Mitchum, Ariane; Coleridge, Marissa B; Farrell, Ruth M
Purpose: The clinical introduction of innovative prenatal genetic technologies challenges patients and providers to find new ways of fostering informed decision-making in a setting characterized by complexity and uncertainty. As prenatal genetic technology advances, important questions remain about how to structure patient-centered conversations that effectively prepare pregnant patients to make informed choices about the different genetic conditions for which this new form screening may be used. Methods: Focus groups were conducted with 23 pregnant women to identify informational needs and decision-making preferences regarding emerging and anticipated applications of cell-free fetal DNA screening, the newest form of prenatal genetic screening. Results: Participants were in favor of obtaining more genetic information about the fetus than provided by conventional screens but acknowledged the challenges inherent in navigating the unique complexities of the decision-making process. The provider–patient relationship was seen as an important resource to navigate the associated uncertainties at each stage of the screening process. Participants emphasized the need for initiatives to support a personalized, accurate, and unbiased discussion about prenatal genetic risk and assessment. Conclusion: Continued advances in prenatal genetic screening call for new approaches to structure patient-centered communication to facilitate increasingly complex decisions about fetal genetic risk and assessment.